(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
It has been rumored that soils around schools in the US are contaminated with lead, which is known to be harmful to children, and is known to inhibit plant growth. The purpose of this study is to investigate the growth of plants in soil sampled from US schools to see if decreased plant growth can indicate lead contamination before testing is done. After comparing the time until germination, height, and root length of radishes grown in soil from the surrounding area of the school to that of those grown in uncontaminated soil, we found that radishes grown in soil from schools germinated at a rate 38% slower than radishes grown in uncontaminated soil (HR = 0.62, 95% CI 0.33-1.2, Ptrend = 0.13). The mean radish heights between the two groups were also found to be significantly different (p = 0.12). Decreased plant growth may serve as an indicator for soil contamination before other laboratory tests are done. It is recommended that further testing for lead and other toxins should be conducted on the soil of the surrounding area, and larger studies with multiple species of plants should be conducted to see if these trends could be applied to the general plant population around schools. Int. J. Agril. Res. Innov. Tech. 10(1): 94-96, June 2020